Positive thinking elevates tolerance: Experimental effects of happiness on adolescents' attitudes toward asylum seekers. (April 2018) - Tenenbaum, Harriet R; Capelos, Tereza; Lorimer, Jessica; Stocks, Thomas
Inducing emotional reactions toward social groups can influence individuals' political tolerance. This study examines the influence of incidental fear and happiness on adolescents' tolerant attitudes and feelings toward young Muslim asylum seekers. In our experiment, 219 16- to 21-year-olds completed measures of prejudicial attitudes. After being induced to feel happiness, fear, or no emotion (control), participants reported their tolerant attitudes and feelings toward asylum-seeking young people. Participants assigned to the happiness condition demonstrated more tolerant attitudes toward asylum-seeking young people than did those assigned to the fear or control conditions. Participants in the control condition did not differ from participants in the fear condition. The participants in the happiness condition also had more positive feelings toward asylum-seeking young people than did participants in the control condition. The findings suggest that one way to increase positive attitudes toward asylum-seeking young people is to improve general emotional state.